CRITICAL ANALYSIS ON INTEGRATION OF PHARMACOGENOMICS INTO NURSING AND PHARMACY PRACTICE - Duleem Naseer Mohammed Lsloom, 2Mesfer Jaber Salem Lasloum, 3Hussain Askar Mohammed ALsaloom, 4Hussain Ali Hussain ALsaloom, 5Mohammed Mana Mahdi baniHumayyim, 6Abdulaziz Mohammad hadialyam, 7Moteaha greeaphussine al mojabah, 8Nourah Ali HussienALmukalas; 9Ghaliah Ali HussienAlmukalas, 10Norah salemhamadalyami, 11Abdulaziz Nasser Mohammed Lsloom, 12Jaber Asker M Lasloom (Chelonian Research Foundation, 2022)
This article investigates the integration of pharmacogenomics into nursing practice and drug storage, a potential zone of change in clinical practice. Pharmacogenomics analyzes how hereditary qualities influence a person's reaction to drugs and the potential to adjust treatment by fitting treatment plans to a patient's hereditary cosmetics. Through a review , this article assesses the current state of pharmacogenomics integration. Audits applications, present discoveries and examines what comes about. This comprehensive survey points out challenges and opportunity and gives a heading for advancing pharmacogenomics into persistent care and pharmacy. Keywords: Pharmacogenomics, nursing practice, pharmacy practice, personalized medicine, healthcare integration.